The digital paradox in social innovation: the interplay between digital maturity and business model innovation - Herrera-Ballesteros, Juan; De-las-Heras-Rosas, Carlos Javier; Mota Veiga, Pedro (Emerald, 2026)
This study aims to analyse how the business environment and digital maturity influence companies' ability to develop social innovation, and to explore the moderating role that business model innovation (BMI) can play in these relationships. The research seeks to provide new evidence on the interaction between internal capabilities and external contexts in the generation of innovation with social impact. The research is based on data from Eurobarometer Flash 486, which includes a representative sample of 12,615 companies in the European Union. Using a multivariate regression approach, the individual and combined effects of the business environment, digital maturity and business model innovation on social innovation are evaluated. The theoretical framework integrates the Resource-Based View (RBV), Dynamic Capabilities Theory (DCT), Open Innovation Theory, Institutional Theory and Social Innovation Systems. The results confirm that both a favourable business environment and greater digital maturity are positively associated with social innovation. However, the most relevant finding shows a negative moderating effect of the BMI on the relationship between digital maturity and social innovation, suggesting organisational tensions arising from simultaneous digital and structural transformations, such as resource overload and ambidexterity challenges in balancing efficiency and social goals. This result underscores the non-linear nature of capability interactions and the importance of proper strategic alignment. On its own, digital maturity has a positive and significant effect, establishing itself as a key organisational capability for addressing social challenges through innovative solutions. This work contributes to a more systemic and contingent understanding of social innovation in organisations. Integrating technological, contextual, and strategic lenses, we challenge the assumption of linear complementarity among capabilities and, using paradox theory, theorize the tensions in capability orchestration that shape social innovation outcomes. The findings yield practical implications for managers and policymakers, including sector-specific guidance for organisations in education and healthcare. They also open new research avenues on organisational ambidexterity and capability orchestration in sustainability-oriented companies.
Keywords: Empresas; Innovaciones tecnológicas; Alfabetizacion digital; Industria - Aspectos sociales; Social innovations; Business environment; Digital maturity; Business model innovation